Biomass estimates and harvest strategies for the Western Australian Octopus aff. tetricus fishery. (21st August 2019) - Hart, Anthony M; Murphy, Dave; Hesp, S Alex; Leporati, Stephen
Abstract: Octopus aff. tetricus is the target of Australia's most significant octopus fishery. We utilized both fishery-independent surveys and fishery data from spatially detailed catch and effort logbooks to examine distribution and abundance across the spatial and depth ranges of the population. From this, a harvest strategy was developed to form the basis for monitoring, assessment, and management. Octopus aff. tetricus is abundant and widely distributed in Western Australia, with a biomass density range of 150–1000 kg km −2 . This is comparable to Octopus vulgaris fisheries in the Mediterranean and sub-Saharan Africa. From an estimated habitat area of 20 073 km 2, total biomass on the West Coast was estimated to be a minimum of 3600 tonnes whole weight with 90% certainty. At the current annual catch of 300 tonnes, overall population exploitation rate is low, given the high natural productivity of the species, which has a maximum age of 1.5 years and two recruitment pulses per year. A formal species name for O. aff. tetricus is required so its contribution to the Australian cephalopod fisheries harvest can be officially recognized.